Prospecção de substâncias orgânicas e de formulações do óleo essencial de Pogostemon cablin Benth. (Lamiaceae) para o controle de Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae) - Pompermayer, Katiane (2023)
The fall armyworm Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae) is an insect with highly destructive potential for crops, which in recent years has assumed a wide geographic distribution, which justifies the search for new molecules to your control. In this study, three approaches were employed in order to search for new tactics for the management of this insect: i) the toxicity of 5 synthetic organic substances, previously selected through computational screening because they complexed with the ecdysone receptor, were evaluated; ii) the sublethal effect of the essential oil (EO) of Pogostemon cablin (Blanco) Benth (Lamiaceae) on the life cycle of S. frugiperda in a food intake assay was determined; iii) the toxicity of a nanoemusion of P. cablin EO and of an inclusion complex of β-cyclodextrin (β-CD) with P. cablin EO in a food intake assay was studied. Of the substances selected for complexing with the nuclear ecdysone receptor, the substance ZINC15969575 obtained a significant reduction in the mass of insects and changes in morphometric parameters, such as: reduction in body length, length and width of the head capsule. From this approach, it can be concluded that the substance ZINC15969575 can be used as a model for the synthesis of new molecules to be used for the control of S. frugiperda. P. cablin EO was highly toxic to S. frugiperda caterpillars (LC50 = 0.42 ± 0.014; LC90 = 0.79 ± 0.049 µg de OE/mL de dieta). It is noteworthy that this EO was more toxic than the positive control, neem oil. Furthermore, when analyzing the effect of sublethal doses (LC50 = 0.42 ± 0.014; LC25 = 0.30 ± 0.0143 µg de OE/mL de dieta) on the life cycle of the insect, it was verified: increase in the larval period, reduction in the mass of the pupae, reduction in the emergence rate of adults and reduction in the fecundity of mated females. With regard to the EO formulations, no significant difference was found for the toxicity of the nanoemulsified EO and its natural form. However, there is a reduction in the toxicity of EO when complexed with β-CD. It is possible that β-CD prevented the release of compounds present in the EO with insecticidal activity. New tests with a view to evaluating the potential of the P. cablin EO nanoemulsion under semi-field and field conditions should be conducted.